ATMOSPHERIC CIRCULATION TRANSITIONAL PERIOD FEATURES AND VARIATIONS OF SPRINGBEGINNING DATES IN CENTRAL CISCAUCASIA - V. I. Volkova; G. K. Badakhova; M. V. Barekova; G. Kaplan (Наука. Инновации. Технологии)
Introduction. The goal of the present study is to investigate atmospheric circulation over Central Ciscaucasia during the transition period from winter to spring. The second goal of the study is to calculate and analyses the air temperature regime in February and March. The third goal of the study is defining dates of the average daily air temperature stable transition through 0 ºC upwards. The article addresses the change in these characteristics in the XX and XXI centuries and the calculation of standard climatic variables for the 1991-2020 reference 30-years period. Materials and methods of the research. The present study was based on the Hydrometeorological Center of Russia and Stavropol CGMS archive synoptic maps. The weather observation data recorded by 16 meteorological stations in the Stavropol Territory in 1991-2020, data from the Climate Reference Book of the USSR [17] and the monograph “Stavropol Territory: modern climatic conditions” [4] were used for the analyses of the temperature regime and spring onset date estimation. The study based on synoptic, physical-statistical and regression analysis methods. The results of the study and their discussion. The synoptic situation, typical for the moment of spring onset in Central Ciscaucasia, was revealed. The average February and March air temperature values on spring onset dates in different landscapes of the Central Ciscaucasia were estimated, and their fluctuations during this period were studied. The earliest and latest spring onset dates and the ratio of early and late spring onsets were determined. The characteristic of the dominant trend in long-term air temperature changes and the assessment of spring onset date change in the region were given. Conclusions. The atmospheric circulation system over the Central Ciscaucasia during the transition period from winter to spring and the synoptic situation, which repeats with slight variations on all dates of the stable transition of air temperature through 0 °C, were described. The present study showed a temperature increase in February and March. The most notable temperature increase was recorded in the XXI century. Despite pronounced fluctuations from year to year, the mean spring onset dates shifted to earlier dates in each of the considered long-term periods. Currently, the standard climatic norm for the spring onset in Central Ciscaucasia is the 18th of February.